Differences in postperinatal infant deaths between north and southern Derbyshire. Issue 12 (December 1991) - Newlands, M; Adamson, E; Ghulam, S; Saleh, M; Emery, J L
Abstract : In depth confidential inquiries on all post-perinatal infant deaths were carried out for two years in North and Southern Derbyshire District Health Authorities in order to explore why the postperinatal death rates and cot death rates have been consistently higher in Southern than in North Derbyshire. It was found that the death rates for probably inevitable deaths and for 'idiopathic' cot deaths were the same in both districts. The differences in the death rates lay in the group of partly explained cot deaths. Adverse social factors associated with each death were recorded and an estimate made of their relevance to the individual deaths. The group of deaths most amenable to intervention was those of category B (partly explained cot deaths). As judged by the Jarman index there are more areas of deprivation in Southern than in North Derbyshire.